CdTe QDs functionalized mesoporous silica nanoparticles loaded with conjugated polymers: A facile sensing platform for cupric (II) ion detection in water through FRET. (February 2015) - Sha, Jie; Tong, Cuiyan; Zhang, Haixia; Feng, Lijuan; Liu, Bingxin; Lü, Changli
Abstract: This paper reported a facile method for fabricating CdTe quantum dots decorated fluorescent mesoporous silica nanoparticles containing poly(p-phenylenevinylene) by electrostatic interaction in aqueous solution. The resulted fluorescent hybrid nanomaterials showed the dual-emission centered at 500 nm and 717 nm, which can be used as a fluorescent probe to detect Cu 2+ in water through fluorescence resonance energy transfer. Cu 2+ can be captured by the amino groups of the polyethyleneimine to form an absorbent complex, resulting in a strong quenching of red-emission from CdTe quantum dots on the surface of nanoparticles via energy transfer. However, the green-emission of poly(p-phenylenevinylene) remained. Therefore the addition of Cu 2+ induced the fluorescent evolution of the nanoprobe from red to green. The nanoprobe provided an efficient platform for the sensing of Cu 2+ with a detection limit of 31.2 nM. Compared with pure quantum dots, the nanoprobe can distinguish Cu 2+ from Hg 2+ . Graphical abstract: A facile strategy for fabricating CdTe QDs decorated fluorescent mesoporous silica nanoparticles containing poly(p-phenylenevinylene) by electrostatic interaction in aqueous solution has been reported. This hybrid nanomaterial can be used as a fluorescent probe to detect Cu 2+ through fluorescence resonance energy transfer. The resulted nanoprobe can distinguish Cu 2+ from other interfering mental ions efficaciously. The nanoprobe provided an efficient platform for the sensing of Cu 2+ with a detection limit of 31.2 nM. Highlights: A novel PPV@MSN@CdTe nanoprobe for Cu 2+ was fabricated via electrostatic interaction. The nanoprobe exhibited the dual fluorescent emission of red-light from CdTe QDs and green-light of PPV. The probe can selectively detect Cu 2+ via FRET, while the green-emission of PPV remains. The nanoprobe can efficaciously distinguish Cu 2+ from other interfering mental ions, especially Hg 2+ . The nanoprobe provided an efficient platform for the sensing of Cu 2+ with a detection limit of 31.2 nM.